Kernel methods in bioengineering, signal and image processing - Camps-Valls, Gustavo, 1972-; Rojo-Álvarez, José Luis, 1972-; Martínez-Ramón, Manel, 1968- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book presents an extensive introduction to the field of kernel methods and real world applications. The book is organized in four parts: the first is an introductory chapter providing a framework of kernel methods; the others address Bioegineering, Signal Processing and Communications and Image Processing"--Provided by publisher.